Pelatihan Regulasi Emosi Sebagai Upaya Meningkatakan Kesejahteraan Subjektif pada Guru Sekolah Luar Biasa - Putri, Dwi Widarna Lita; Niagara, Siska Triana; Nuraeni, Deva Aulia (Jurnal Bimbingan dan Konseling Islam, 2023)
This research aims to determine the effect of emotional regulation training on increasing subjective well-being in Special School Teachers (SLB). The subjects in this research were 20 SLB teachers. The hypothesis proposed in this research is that there is a difference in the subjective well-being of special school teachers who take emotional regulation training and special school teachers who do not take emotional regulation training. The research design used was a control group design. Quantitative analysis uses an independent sample t-test to determine whether or not there is an effect of emotion regulation training on increasing subjective well-being in the experimental group that was given emotion regulation training and the control group that was not given emotion regulation training. The results of the research, in the form of all aspects of subjective well-being, show that there are very significant differences, SLB teachers in the control group and the experimental group who were given treatment with the final subjective well-being test score in the form of life satisfaction with a value of p=0.003 (P<0.01), affect positive with a value of p=0.003 (P<0.01) and negative affect with a value of P=0.003 (P<0.01).